Low-temperature dynamics of matrix isolated methane molecules in fullerite C60. The heat capacity, isotope effects - Bagatskii, M.I.; Manzhelii, V.G.; Sumarokov, V.V.; Dolbin, A.V.; Barabashko, M.S.; Sundqvist, B. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2014)
The heat capacity of the interstitial solid solution (CH4)0.4C60 has been investigated in the temperature interval 1.4–120 K. The contribution of CH4 molecules to the heat capacity of the solution has been separated. The contributions of CH4 and CD4 molecules to the heat capacity of the solutions (CH4)0.40C60 and (CD4)0.40C60 have been compared. It is found that above 90 K the character of the rotational motion of CH4 and CD4 molecules changes from libration to hindered rotation. In the interval 14–35 K the heat capacities of CH4 and CD4 molecules are satisfactorily described by contributions of the translational and libration vibrations, as well as the tunnel rotation for the equilibrium distribution of the nuclear spin species. The isotope effect is due to mainly, the difference in the frequencies of local translational and libration vibrations of molecules CH4 and CD4. The contribution of the tunnel rotation of the CH4 and CD4 molecules to the heat capacity is dominant below 8 K. The isotopic effect is caused by the difference between both the conversion rates and the rotational spectra of the nuclear spin species of CH4 and CD4 molecules. The conversion rate of CH4 molecules is several times lower than that of CD4 ones. Weak features observed in the curves of temperature dependencies of the heat capacity of CH4 and CD4 molecules near 6 and 8 K, respectively, are most likely a manifestation of first-order polyamorphic phase transitions in the orientational glasses of these solutions.